Effect of maltodextrin concentration on the organoleptic characteristics, proximate composition, and antioxidant activity of spray-dried turmeric–tamarind powder - Al Fia Febriani; Mia Srimiati (Arsip Keilmuan Gizi (AKG), 2026)
Dysmenorrhea is a common menstrual pain complaint among adolescent girls. Turmeric–tamarind beverage has potential as an herbal alternative; therefore, the development of an instant powder using spray drying is needed to improve product practicality. This study aimed to evaluate the effect of maltodextrin concentration on the organoleptic properties of turmeric–tamarind powder and its reconstituted beverage, and to describe the proximate composition, curcumin content, and antioxidant activity of the product. A completely randomized design with one factor was applied, namely maltodextrin concentration 10% (P1 = 100 g), 20% (P2 = 200 g), and 30% (P3 = 300 g) per 1,000 g turmeric–tamarind solution prior to spray drying. Organoleptic evaluation was conducted by 35 semi-trained panelists using a 1–7 hedonic scale and analyzed using Kruskal–Wallis followed by Mann–Whitney tests. The results showed that maltodextrin significantly affected powder color, texture, and overall acceptability, while in the reconstituted beverage it significantly influenced taste and overall acceptability, with the best acceptance observed in P3. Chemical analysis of the selected formulation (P3) showed 89.02% moisture, 10.83% carbohydrate, 0.16% ash, <0.04% protein, <0.02% fat, and 20.88 mg/L curcumin content. Antioxidant activity increased from 4.16% to 6.35% inhibition after spray drying. In conclusion, 30% maltodextrin resulted in the highest sensory acceptance, and the final product retained functional potential as indicated by detectable curcumin content and antioxidant activity.